Pembinaan Komunitas Ramah Lingkungan (Eco Community) Berbasis Pelatihan Green Lifestyle: Eco-Friendly Community Development Through Green Lifestyle Training - Restya, Winda Putri Diah; Septiawati, Sriana (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Environmental challenges in Indonesia, such as deforestation, water pollution, and a lack of public awareness regarding environmental sustainability, present significant obstacles to achieving sustainable development goals. Despite growing awareness of environmental issues, eco-friendly behaviors, and lifestyle changes among the population remain limited. This community service initiative seeks to establish a "Pilot Village" in the form of an Eco-Community, focused on fostering sustainable habits through Green Lifestyle training. The program employs a combination of outreach, participatory training, focus group discussions, and hands-on activities, all of which engage community members directly. Results from a pre-test on environmental awareness revealed that while community members demonstrated a high level of awareness (89.3%), their actions were not yet fully aligned with this understanding, as reflected in the behavior scores (67.8%). However, the initiative has shown positive outcomes, with significant improvements in community knowledge and participation in sustainable practices such as reducing plastic use and implementing better waste management systems. In conclusion, this program has successfully enhanced environmental awareness and promoted responsible behaviors within the community. Furthermore, it has created a replicable model for developing eco-friendly village communities, which can be adapted and applied in other regions.